2019
DOI: 10.1007/s00268-019-05015-w
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Gender, Surgery and Mortality for Patients Treated at Médecins Sans Frontières Trauma Centre in Kunduz, Afghanistan

Abstract: Introduction There is paucity of literature describing type of injury and care for females in conflicts. This study aimed to describe the injury pattern and outcome in terms of surgery and mortality for female patients presenting to Médecins Sans Frontières Trauma Centre in Kunduz, Afghanistan, and compare them with males. Materials and Methods This study retrospectively analysed patient data from 17,916 patients treated at the emergency department in Kunduz between January and September 2015, before its destr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…Divergence of findings between community- and facility-based methods in our study included the barriers “ cultural norms ” with weak evidence from community qualitative methods in contrast to strong facility-based evidence. Community social and cultural perceptions and gender-based factors are known barriers to women seeking care [ 4 , 22 , 30 , 65 , 66 ]. Male household heads can have higher disease severity thresholds for financing health-seeking, more readily financing healthcare for male household members [ 67 ].…”
Section: Discussionmentioning
confidence: 99%
“…Divergence of findings between community- and facility-based methods in our study included the barriers “ cultural norms ” with weak evidence from community qualitative methods in contrast to strong facility-based evidence. Community social and cultural perceptions and gender-based factors are known barriers to women seeking care [ 4 , 22 , 30 , 65 , 66 ]. Male household heads can have higher disease severity thresholds for financing health-seeking, more readily financing healthcare for male household members [ 67 ].…”
Section: Discussionmentioning
confidence: 99%
“…This contrasts sharply with reports from other armed conflicts where females have constituted up to 43% of the treated patients. 153,154 The observed difference may be explained by the fact that ICRC facilities are devoted to only treating patients with weapon-related injuries, whereas other health care facilities in conflict areas may also treat patients with conditions that are not weapon-related. This notion is supported by a report, published in 2016, from the Médicines sans Frontières (MSF) trauma center in Kunduz, Afghanistan, that operated in a similar context as the ICRC hospital in Peshawar.…”
Section: Descriptive Findings (Papers I -Iii)mentioning
confidence: 99%
“…This is more or less the opposite of what Tounsi et al reported in 2019, from the MSF Trauma Centre in Kunduz, Afghanistan. 154 They found that females arrived later and were less likely to undergo surgery compared to males. However, less than 10% of the females treated at MSF's Trauma Center in Kunduz had weapon-related injuries, whereas ICRC facilities, as mentioned earlier, only treated weapon-related injuries.…”
Section: Descriptive Findings (Papers I -Iii)mentioning
confidence: 99%
See 1 more Smart Citation
“…6 In recent years, the number of civilian targets in armed conflict areas has increased as have the challenges associated with managing their injuries. 7,8 Still, research conducted on conflict-related injuries continues to focus on military rather than civilian populations. 9,10 Few studies have focused on gunshot and bomb blast wounds in civilians.…”
Section: Introductionmentioning
confidence: 99%